2021
DOI: 10.1016/j.ijid.2020.10.066
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of non-pharmaceutical interventions on COVID-19 transmission in 190 countries from 23 January to 13 April 2020

Abstract: Highlights Non-pharmaceutical interventions was effective in reducing COVID-19 transmission. Social distancing is more effective than the other NPIs in containing COVID-19. Two or more synchronous NPIs are more effective than a single type of NPIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
252
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(265 citation statements)
references
References 23 publications
7
252
1
5
Order By: Relevance
“…The list does not come as surprise considering the epicenter of the pandemic, data availability as well as the evolution of the pandemic in USA and Europe. However, few models in the sample consider hundreds of countries [22] , [44] , [45] , [45] , [46] , [47] . Second, this body of research has been published by authors with affiliations in countries.…”
Section: Epidemic Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…The list does not come as surprise considering the epicenter of the pandemic, data availability as well as the evolution of the pandemic in USA and Europe. However, few models in the sample consider hundreds of countries [22] , [44] , [45] , [45] , [46] , [47] . Second, this body of research has been published by authors with affiliations in countries.…”
Section: Epidemic Modelsmentioning
confidence: 99%
“…These approaches have been applied to the COVID-19 pandemic to gather information about the key epidemiological parameters and quantify the effects of NPIs by looking at deviations from expected and/or initial trends [24] , [46] , [124] , [125] , [126] , [127] , [129] , [130] , [131] , [132] , [133] , [134] . Let’s dive into some details.…”
Section: Epidemic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…22 This good news does not mean that awareness about transmission of the disease is unnecessary anymore. A study revealed the importance of non-pharmaceutical interventions (NPIs) on reducing the reproduction number of COVID-19 virus 23 but may limit data in Indonesia about it. Understanding KAP is essential to identify and overcome false rumours about a disease that may negatively influence community prevention behaviour, including NPI.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of specific medicine and vaccine to counter the virus, non-pharmaceutical interventions (NPIs) play an important role to control epidemics. Bo et al 8 divides the implemented NPIs into four categories: mandatory face mask in public, isolation or quarantine, social distancing and traffic restriction. There have been several researches to evaluate the effectiveness of these NPIs.…”
Section: Introductionmentioning
confidence: 99%